1996
DOI: 10.1093/gerona/51a.4.m152
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Functional Outcome of Total Knee Replacement: A Prospective Study

Abstract: Psychosocial variables are significantly related to total knee replacement functional outcome. Assessment of baseline psychological and social functioning may identify a subset of patients at risk for worse outcome. Specific interventions for these patients should be developed and evaluated as components of patient management prior to and after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
2
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 14 publications
2
68
2
4
Order By: Relevance
“…The literature has suggested psychologic distress is an important predictor for poor outcome after knee arthroplasty [1,2,5,14,34,47], but we found no studies that quantified the effects of specific psychologic disorders or health-related beliefs on pain or physical function outcome. Ayers et al [2] found that patients who had knee arthroplasty with SF-36 MCS scores less than 50 had higher levels of catastrophizing, depression, and anxiety than patients with scores of 50 or greater.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The literature has suggested psychologic distress is an important predictor for poor outcome after knee arthroplasty [1,2,5,14,34,47], but we found no studies that quantified the effects of specific psychologic disorders or health-related beliefs on pain or physical function outcome. Ayers et al [2] found that patients who had knee arthroplasty with SF-36 MCS scores less than 50 had higher levels of catastrophizing, depression, and anxiety than patients with scores of 50 or greater.…”
Section: Discussionmentioning
confidence: 77%
“…They did not, however, report whether these specific psychologic distress measures predicted outcome independent of the more general SF-36 MCS score. Given that most studies have used general measures of psychologic distress in lieu of specific measures of disorders or pain-related beliefs [1,2,5,14,34,47], a study of these more specific constructs and their impact is needed. We hypothesized that one or more of the specific psychologic disorders or health-related beliefs that we studied would predict poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expectations and motivation of the patient certainly play a role [16], but previously the qualities of a patient have not been very good at predicting the results [15]. The study on the effect of gender or obesity has been conflicting [13], as well as research on the effect of number of comorbidities [15,17].…”
Section: Introductionmentioning
confidence: 99%